Experimental study of tribological and mechanical properties of TiN coating on AISI 52100 bearing steel. (September 2018) - Uddin, Ghulam Moeen; Khan, Awais Ahmad; Ghufran, Muhammad; Tahir, Zia-ur-Rehman; Asim, Muhammad; Sagheer, Muhammad; Jawad, Muhammad; Ahmad, Jawad; Irfan, Muhammad; Waseem, Bilal
The surface coating is one of the novel approaches to enhance the performance and durability of the mechanical components by decreasing the wear and friction among two interacting bodies. In this study, tribological and mechanical properties of titanium nitride (TiN) coatings were investigated on the AISI 52100 bearing steel deposited by low-temperature physical vapor deposition system. Surface morphology and elemental composition of the TiN coating were analyzed by scanning electron microscope and energy-dispersive X-ray spectrum, respectively. Substrate surface roughness and coating thickness of TiN were varied for correlative analysis among adhesion, mechanical, and tribological properties. Scratch and tribo tests were performed for evaluating the adhesion and tribological properties, respectively. Samples having the substrate surface roughness (0.2 ± 0.05 µm) and the coating thickness of more than 2.83 µm presented relatively better adhesion, wear resistance, and lower coefficient of friction of the TiN coating.